Using Dialectic Thematic Analysis in dark tourism: Combining deductive and inductive reasoning in a modular method. (September 2021) - MacCarthy, Martin
Abstract: This study combines the results of two antithetical research processes: induction and deduction. Using a prescribed dialectic method commemorative pilgrimage at two non-substitutable sites is explored. A metamodel, comprising an amalgam of published commemorative models and ideas is first constructed and used as the project's interpretive frame. Parsing the metamodel produces 17 constructs: four of which are motives (inputs) and 11 of which are typified behaviours (outputs). The combined data from two Australian memorials; one in Western Australia and one in France is then analysed using the metamodel as representative of existing theory. The constructs are then deduced whilst simultaneously informing the induction of three commemorative themes. The data supports the view that motives driving pilgrimage to commemorative destinations are a function of three push motives: Obligation, Association, Individuation, and one pull motive, Manipulation. Contradicting alternate notions of dark tourism, the findings point to death and suffering associated with memorial tourism as being incidental, and more instrumental than autotelic.